Disrupting the SKN-1 homeostat: mechanistic insights and phenotypic outcomes - Turner, Chris D.; Ramos, Carmen M.; Curran, Sean P. (Frontiers in Aging, 2024)
The mechanisms that govern maintenance of cellular homeostasis are crucial to the lifespan and healthspan of all living systems. As an organism ages, there is a gradual decline in cellular homeostasis that leads to senescence and death. As an organism lives into advanced age, the cells within will attempt to abate agerelated decline by enhancing the activity of cellular stress pathways. The regulation of cellular stress responses by transcription factors SKN-1/Nrf2 is a well characterized pathway in which cellular stress, particularly xenobiotic stress, is abated by SKN-1/Nrf2-mediated transcriptional activation of the Phase II detoxification pathway. However, SKN-1/Nrf2 also regulates a multitude of other processes including development, pathogenic stress responses, proteostasis, and lipid metabolism. While this process is typically tightly regulated, constitutive activation of SKN-1/Nrf2 is detrimental to organismal health, this raises interesting questions surrounding the tradeoff between SKN-1/Nrf2 cryoprotection and cellular health and the ability of cells to deactivate stress response pathways post stress. Recent work has determined that transcriptional programs of SKN-1 can be redirected or suppressed to abate negative health outcomes of constitutive activation. Here we will detail the mechanisms by which SKN-1 is controlled, which are important for our understanding of SKN-1/Nrf2 cytoprotection across the lifespan.